Machine Translation : Need of the Time - Devale, PR; Patil, SH (International Journal of Computer Sciences and Engineering, 2025)
Machine Translation provides a solution in breaking the language barrier so that humans can transform information; it is important application of Natural Language Processing. There are many different languages spoken in this world. Among those language English is the global language. Though it is global language many people can’t understand English especially in rural areas of India. From the many years machine translation has been a topic of research. There are many methods and techniques for achieving the machine translation. In India many regional languages are spoken. The mother of all these native languages in India is Sanskrit. A great storage of knowledge with subjects like medicine, mathematics, Geography, Geology, Astronomy, philosophy and many others is kept alive and fresh in Sanskrit for thousands of years. Hence here we have chosen Sanskrit as the target language. Most of the literature, political documents etc. are available in English. So we have chosen English as a source language. This paper illustrates about the language translation mechanism which converts English text to Sanskrit text using Rule Based approach. Presently work on machine translation in India is performed at various locations like JNU, IIT Kanpur, CDAC Pune and many more.